Infusion of Silver–Polydopamine Particles into Polyethersulfone Matrix to Improve the Membrane’s Dye Desalination Performance and Antibacterial Property - Hazel Lynn C. Maganto; Micah Belle Marie Yap Ang; Gian Vincent C. Dizon; Alvin R. Caparanga; Ruth R. Aquino; Shu-Hsien Huang; Hui-An Tsai; Kueir-Rarn Lee (Membranes, 2021)
The advancement in membrane science and technology, particularly in nanofiltration applications, involves the blending of functional nanocomposites into the membranes to improve the membrane property. In this study, Ag-polydopamine (Ag-PDA) particles were synthesized through in situ PDA-mediated reduction of AgNO3 to silver. Infusing Ag-PDA particles into polyethersulfone (PES) matrix affects the membrane property and performance. X-ray photoelectron spectroscopy (XPS) analyses confirmed the presence of Ag-PDA particles on the membrane surface. Field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM) describe the morphology of the membranes. At an optimum concentration of Ag-PDA particles (0.3 wt % based on the concentration of PES), the modified membrane exhibited high water flux 13.33 L∙m−2∙h−1 at 4 bar with high rejection for various dyes of >99%. The PESAg-PDA0.3 membrane had a pure water flux more than 5.4 times higher than that of a pristine membrane. Furthermore, in bacterial attachment using Escherichia coli, the modified membrane displayed less bacterial attachment compared with the pristine membrane. Therefore, immobilizing Ag-PDA particles into the PES matrix enhanced the membrane performance and antibacterial property.